2021
DOI: 10.3390/genes12040490
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies and Prediction of Tan Spot (Pyrenophora tritici-repentis) Infection in European Winter Wheat via Different Marker Platforms

Abstract: Tan spot, caused by the fungus Pyrenophoratritici-repentis (Ptr), is a severe foliar disease of wheat (Triticumaestivum L.). Improving genetic resistance is a durable strategy to reduce Ptr-related losses. Here, we dissected Ptr-infection’s genetic basis in 372 European wheat varieties via single sequence repeats (SSR) in addition to 35k and 90k single nucleotide polymorphism (SNP) marker platforms. In our phenotypic data analyses, Ptr infection showed a significant genotypic variance and a significant negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Similarly, in a study of tan spot resistance in the bread wheat variety Ernie, no significant correlations were detected between tan spot severity with either DH or PH [83]. However, many other studies reported a negative correlation between DH or PH with disease resistance; indeed, in a recent study of resistance of 372 European wheat varieties to tan spot disease in Germany, a highly significant negative correlation of tan spot infection with PH and a moderate negative correlation with DH were reported, indicating that plant height and late heading might be potential tan spot disease escape traits, therefore, indicating a role of plant height in disease expression [84]. In another study that characterized 358 European winter wheat cultivars and 14 spring wheat cultivars for their resistance to tan spot in Germany, the authors showed that shorter plants showed a tendency to be more susceptible while no significant correlation between Ptr resistance and DH was established [85].…”
Section: Correlation Of Tan Spot Infection With Plant Height and Days...mentioning
confidence: 94%
“…Similarly, in a study of tan spot resistance in the bread wheat variety Ernie, no significant correlations were detected between tan spot severity with either DH or PH [83]. However, many other studies reported a negative correlation between DH or PH with disease resistance; indeed, in a recent study of resistance of 372 European wheat varieties to tan spot disease in Germany, a highly significant negative correlation of tan spot infection with PH and a moderate negative correlation with DH were reported, indicating that plant height and late heading might be potential tan spot disease escape traits, therefore, indicating a role of plant height in disease expression [84]. In another study that characterized 358 European winter wheat cultivars and 14 spring wheat cultivars for their resistance to tan spot in Germany, the authors showed that shorter plants showed a tendency to be more susceptible while no significant correlation between Ptr resistance and DH was established [85].…”
Section: Correlation Of Tan Spot Infection With Plant Height and Days...mentioning
confidence: 94%
“…In addition, in this study, PH was significantly negatively correlated to adult-stage resistance, indicating that the shorter plants are the more susceptible to TS. This could also indicate an escape effect, as illustrated in the study of Muqaddasi et al [ 73 ], as taller plants have more space between nodes, thus making the spread of conidia from lower leaves to upper leaves difficult. This suggests that selection for increased height would help in contributing to escape from TS.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that selection for increased height would help in contributing to escape from TS. Many studies delt with correlation between wheat resistance to TS and PH, where conflicting results were found; while some studies concluded that there was no significant effect of PH on TS development [ 14 , 51 , 74 , 75 ], other studies concluded that plant height may affect TS severity [ 73 , 76 ]. Many factors could have contributed to these different outcomes, including the use of genetically different germplasms, the size of the panel, the conduction of these experiments in different environments, environmental or epidemiological factors, and the variable Ptr populations used in the conduction of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GWAS method has been successfully applied in different plants for various traits. Different wheat traits have been studied using GWAS including agronomic traits (Safdar et al 2020; Pang et al 2020), quality (Yang et al 2020; Muqaddasi et al 2020), drought stress (Abou-Elwafa et al 2021; Shokat et al 2020; Rahimi et al 2019), leaf rust (Spakota et al 2019; Muqaddasi et al 2021), and stem rust resistance (Saremi et al 2021; Gao et al 2017). For leaf rust resistance, Spakota et al (2019) employed GWAS to identify related genomic areas in wheat genotypes, and eleven QTLs (Quantitative Trait Loci) were identified on nine chromosomes.…”
Section: Introductionmentioning
confidence: 99%